Penentuan Jenis dan Ukuran fasilitas Pokok Tempat Pemasaran Ikan di Desa Pakningasal Kecamatan Bukitbatu Kabupaten Bengkalis - Harahap, Alpin Septiyan; Zain, Jonny; Hutauruk, Ronald M. (Fakultas Perikanan dan Kelautan Universitas Riau, 2018)
The main facility is a facility at a fishing port used for tied and docked vessels for fish-ing vessels as well as minimizing natural disruption and shipping safety. This research was conducted in December 2016 in Pakningasal Village, Bukitbatu District, Bengka-lis Regency. The purpose of this research is to determine the type and size of the main facility of dock and port pool. Research method used in this research is survey method by doing direct observation. Data collection is done by collecting information about the main activities and activities that exist in the Marketing Place Fish Village Pak-ningasal. From the results of research conducted then required size for unloading pier is 9.89 m and length for loading area is 42,075 m so that the total length of the dock required is 51,965 m. The types and types that are being constructed with construction. The vast harbor pool area is 1321,71 m2 and the required depth of the pond is 1.3 m and it is recommended to mount the pool tour in swimming pool.